Decision Support System For Determining The Type Of Workout Using The Fuzzy Analythical Hierarchy Process (F-AHP) In GYM STIKI - I Nyoman Tri Anindia Putra; Ketut Sepdyana Kartini; Ni Komang Ayu Sinariyani; Nia Maharani (Jurusan Teknik Informatika, 2021)
Purpose: Decision Support System for Determining the Type of Workout Using the Fuzzy Analythical Hierarchy Process (F-AHP) Method The STIKI GYM was created to make it easier for trainers to provide training for STIKI GYM participants who carry out workouts at STIKI GYM. Meanwhile, for STIKI GYM participants, the system can make it easier to carry out workout activities according to their respective body loads.Design/methodology/approach: Fuzzy Analythical Hierarchy Process (F-AHP) Method and being tested with black box testingFindings/result: Users can find out workout activities by entering the criteria for body weight, height, and exercise intensity into the system and helping trainers provide training in accordance with the recommendations for workout activities from the Decision Support System for Determining the Types of Workout Using the Fuzzy Analythical Hierarchy Process (F-AHP) Method at STIKI GYM.Originality/value/state of the art: The Decision Support System for determining the Type of Workout is indeed implemented at STIKI GYM by using data support in the form of interview results and participant data from STIKI GYM.